Neuron differentiation and axon growth in the developing wing of Drosophila melanogaster. - Murray, M.A.; Schubiger, M.; Palka, J. (Developmental Biology, 1984)
Sensory neurons in the wing of Drosophila originate locally from epithelial cells and send their axons toward the base of the wing in two major bundles, the L1 and L3 nerves. We have estimated the birth times of a number of identified wing sensory neurons using an X-irradiation technique and have followed the appearance of their somata and axons by means of an immunohistochemical stain. These cells become immunoreactive and begin axon growth in a sequence which mirrors the sequence of their birth times. The earliest ones are born before pupariation and begin axonogenesis within 1 to 2 hr after the onset of metamorphosis; the last are born and differentiate some 12 to 14 hr later. The L1 and L3 nerves are formed in sections, with specific neurons pioneering defined stretches of the pathways during the period between 0 and 4 hr after pupariation (AP), and finally joining together around 12 hr AP. By 16 hr AP the adult complement of neurons is present and the adult peripheral nerve pattern has been established. Pathway establishment appears to be specified by multiple cues. In places where neurons differentiate in close proximity to one another, random filopodial exploration followed by axon growth to a neighboring neuron soma might be the major factor leading to pathway construction. In other locations, filopodial contact between neighboring somata does not appear to occur, and axon pathways joining neural neighbors by the most direct route are not established. We propose that in these cases additional factors, including veins which are already present at the time of axonogenesis, influence the growth of axons through non-neural tissues.